Health resources in a 200,000 urban Indian population argues the need for a policy on private sector health services - Kheya Melo Furtado; Anita Kar (Wolters Kluwer Medknow Publications, 2014)
Background: There are limited primary data on the number of urban health care providers in private practice in developing countries like India. These data are needed to construct and test models that measure the efficacy of public stewardship of private sector health services. Objective: This study reports the number and characteristics of health resources in a 200 000 urban population in Pune. Materials and Methods: Data on health providers were collected by walking through the 15.46 sq km study area. Enumerated data were compared with existing data sources. Mapping was carried out using a Global Positioning System device. Metrics and characteristics of health resources were analyzed using ArcGIS 10.0 and Statistical Package for the Social Sciences, Version 16.0 software. Results: Private sector health facilities constituted the majority (424/426, 99.5%) of health care services. Official data sources were only 39% complete. Doctor to population ratios were 2.8 and 0.03 per 1000 persons respectively in the private and public sector, and the nurse to doctor ratio was 0.24 and 0.71, respectively. There was an uneven distribution of private sector health services across the area (2-118 clinics per square kilometre). Bed strength was forty-fold higher in the private sector. Conclusions: Mandatory registration of private sector health services needs to be implemented which will provide an opportunity for public health planners to utilize these health resources to achieve urban health goals.